CHRONIC WOUNDS : RISK FACTORS AND EVIDENCE-BASED INTERVENTION - Pinem, Veronica Abebia Beginanta; David Sontani Perdanakusuma; Evy Ervianti; Mikiyas Gifawosen Teferi; Harith Ali Al-Taie (Universitas Airlangga, 2025)
Highlights: Identifies key risk factors for chronic wounds and the underexplored role of genetics and immune dysregulation in healing. Explores advanced interventions like smart bandages and bioengineered skin, while addressing accessibility challenges. Highlights the potential of personalized medicine and digital health in improving patient-centered wound care. Abstract: Introduction: Chronic wounds are a pervasive and escalating public health issue, characterized by their inability to progress through the typical phases of healing, resulting in prolonged tissue damage and patient morbidity. Common types include diabetic, pressure, arterial, and venous ulcers. Factors like comorbidities, infection, poor circulation, and inadequate care delay healing. This review aims to explore the risk factors for chronic wounds and evaluate evidence-based interventions to optimize treatment outcomes, thereby improving patient care and reducing healthcare costs. Methods: A thorough literature review was performed using peer-reviewed journals and reliable medical databases, focusing on articles from the past 10 years for relevance. The search used keywords like